(untitled) (Bangladesh Critical Care Journal, 2015)
Adrenal insufficiency means hypo function of the adrenal cortex, usually resulting in low glucocorticoid level and it may be associated with low mineralocorticoid, rarely low adrenal androgen level. It can be categorized into two types: primary and secondary. Primary adrenal insufficiency or Addison’s disease is associated with low cortisol and high ACTH level. Secondary/tertiary adrenal insufficiency is due to pituitary or hypothalamic disorders and is associated with both low cortisol and ACTH level. Among critically ill patients (CIP) adrenal insufficiency is not uncommon. The reported incidence of adrenal insufficiency varies greatly depending on the population of critically ill patients studied, the type of test, cut off levels used, and the severity of illness. Several studies have shown increased mortality in patients with very low or very high baseline cortisol levels. Manifestations of adrenal insufficiency in the critically ill patient are numerous and nonspecific, so clinicians are urged to have a high index of suspicion while taking history and doing physical examination and be alert to important diagnostic clues, such as hyponatremia, hyperkalemia, and hypotension, that are refractory to fluids and vasopressor without any clear causation. In current literature there is no consensus level of cortisol (basal/random/stimulated) in critically ill subjects. But it is shown that both high and low cortisol level is associated with increased mortality. In one study Basal Serum Cortisol <414 nmol/L and > 696 nmol/L is shown as indicative of higher risk among critically ill patients. Even with Septicemia or ARDS all subjects dont suffer from adrenal insufficiency often termed relative adrenal insufficiency or critical illness associated adrenal insufficiency. It has been observed that short term low dose IV hydrocortisone may be beneficial in selective group of patients in intensive care unit (ICU) with critical illness. Diagnosis of adrenal insufficiency associated with critical illness is still challenging for physicians working in ICU. Treatment should be started without delay in emergency situation with Injection Hydrocortisone intravenously or even intramuscularly. Since the condition appears to be common in patients with septic shock, clinicians should have a high index of suspicion for its occurrence in critically ill patients with persistent hypotension despite adequate fluid resuscitation and/or poor hemodynamic response to vasopressor. Adrenal insufficiency associated with other illnesses in ICU are attributed to previous primary or secondary adrenal insufficiency. Treatment with physiologic doses of corticosteroids should be started as soon as possible since short-term treatment carries very few risks and has been shown to decrease both morbidity and mortality. Only suspected cases should be evaluated and could be treated with 100-200 mg Hydrocortisone in divided doses for 5-7 days. Glucocorticoid cannot be recommended as a routine adjuvant therapy in all cases of septic shock or ARDS. But glucocorticoid earned its position among other rescue strategies in subgroups of ICU patients with the highest mortality risk. Steroid use is an art and needs to be used by experienced physician. Otherwise it may do more harm than benefit. Bangladesh Crit Care J March 2015; 3 (1): 27-30